(untitled) (Huellas, 2023)
Production practices in agriculture imply different forms of environmental perception. This is particularly apparent in the case of pollution. From this starting point, we propose to characterize how the arguments of contamination and danger are opposed according to the production styles in a case study located in the southwest of the province of Buenos Aires. We analyze qualitative fieldwork data and recover classic contributions from social anthropology as we consider that contamination is everything that is out of place, disarranged and, therefore, out of our mental configuration. However, what pollutes has an ambivalent meaning because in certain contexts it can also represent order and imply purity. We observe that, although pollution perceptions are organized according to each style of production, they are articulated according to the productive intensification imposed by the development of agrarian capitalism. In this sense, examining the cultural acceptance of agrochemicals and the different perceptions of pollution at stake contributes to understanding the hegemony of a production style that is known to be harmful for the environment and the health of the inhabitants.